The Effect Of Cold Cabbage Leaf Compress On Reducing Pain And Engorgement In Post Partum Mothers In Mundu District Cirebon Regency - Uly Artha Silalahi; Utami Dwi Rizky Amalia; Herni Kurnia (Poltekkes Kemenkes Tasikmalaya, 2026)
Breast engorgement is an example of a problem that often occurs in breastfeeding mothers. Engorgement if not treated immediately can cause mastitis or even breast abscess and inhibit exclusive breastfeeding. Engorgement can be treated pharmacologically or non-pharmacologically. Non-pharmacologically, one of which is cold cabbage leaf compress. Objective: To determine the effect of cold cabbage leaf compress on reducing pain and engorgement in postpartum mothers in Mundu District, Cirebon Regency. Method: Quantitative research using the Quasi Experiment method with a one-group pretest-posttest design. Samples were taken using purposive sampling, with several inclusion and exclusion criteria. The sampling technique used was Accidental Sampling using the Slovin formula with 38 respondents. Results: The results showed that there was an effect of cold cabbage leaf compress on reducing pain and engorgement in postpartum mothers in Mundu District, Cirebon Regency with a p-value of 0.000 (α <0.05) each. Conclusion: Cold cabbage leaf compress can be used as a therapy to reduce pain and engorgement in postpartum mothers in Mundu District, Cirebon Regency. It is hoped that there will be other research related to cabbage leaves, so that we can find the content and also the clear mechanism contained in cabbage leaves that can provide an effect in overcoming breast pain and engorment in postpartum mothers.